Development of Project-Based Learning (PjBL) Teaching Module for the Basic of Metrology Course in the Mechanical Engineering Education Study Program at Sriwijaya University (Jurnal Vokasi Mekanika, 2025)
The focus of this research aims to design a learning module based on the principles of Project Based Learning (PjBL) for the Basic Metrology course in the Mechanical Engineering Education Study Program, Sriwijaya University. Utilizing a Research and Development (R&D) methodology, the study adopts the 4D model, encompassing the stages of Define, Design, Develop, and Disseminate. Validation by a subject matter expert produced an average rating of 3.50 (87.5%), classifying the module as highly valid. Concurrently, evaluation by a media expert yielded an average score of 3.25 (81.37%), situating it within the valid category. Furthermore, a practicality assessment derived from student feedback returned an average score of 3.32 (83.25%), which is categorized as excellent. In the component of creativity and innovation, the module received a score of 3.00 or 75%, suggesting that although the module functions well, there remains room for enhancement to further encourage students’ ability to generate new ideas.